2021
DOI: 10.3390/vaccines9090991
|View full text |Cite
|
Sign up to set email alerts
|

Development and Optimization of an Enzyme Immunoassay to Detect Serum Antibodies against the Hepatitis E Virus in Pigs, Using Plant-Derived ORF2 Recombinant Protein

Abstract: Hepatitis E is an emerging global disease, mainly transmitted via the fecal–oral route in developing countries, and in a zoonotic manner in the developed world. Pigs and wild boar constitute the primary Hepatitis E virus (HEV) zoonotic reservoir. Consumption of undercooked animal meat or direct contact with infected animals is the most common source of HEV infection in European countries. The purpose of this study is to develop an enzyme immunoassay (EIA) for the detection of anti-hepatitis E virus IgG in pig … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…The plantderived S protein in the S and EMS samples was successfully used as coating antigen to detect anti-SARS-CoV2 IgG in serum samples from COVID-19 recovered patients (Figure 6), which shows that plants produced antigenically relevant protein. In this regard it is worth noting that plant-produced diagnostic antigens from other viruses have shown high sensitivity and specificity (Siew et al, 2021;Takova al., 2021), demonstrating the utility of plant expression systems. The data also suggest that induction of an immune response in the human body might also be possible with the plant-made VLPs reported here, as previously demonstrated with a modified S protein by Ward et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…The plantderived S protein in the S and EMS samples was successfully used as coating antigen to detect anti-SARS-CoV2 IgG in serum samples from COVID-19 recovered patients (Figure 6), which shows that plants produced antigenically relevant protein. In this regard it is worth noting that plant-produced diagnostic antigens from other viruses have shown high sensitivity and specificity (Siew et al, 2021;Takova al., 2021), demonstrating the utility of plant expression systems. The data also suggest that induction of an immune response in the human body might also be possible with the plant-made VLPs reported here, as previously demonstrated with a modified S protein by Ward et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…VLP formation was also examined by atomic force and electron microscopy. The collected data confirmed self-assembled VLP particles with very heterogeneous sizes [95,312]. The immunogenicity of the plant-produced HEV 110-610 protein was examined in mice, and it was concluded that immunizations with the recombinant protein induced high titers of specific IgG antibodies in comparison to the negative control group [311].…”
Section: Hepatitis E Virusmentioning
confidence: 54%
“…The transient expression approach was used in conjunction with the highly productive vectors pEAQ-HT and pEff, based on the Cowpea mosaic virus (CPMV) and the potato virus X (PVX), respectively. When a truncated ORF2 (110-610 aa) sequence, cloned into the pEAQ-HT vector, was expressed, it resulted in a protein production rate of 100 µg/g of FW [310], whereas the same sequence cloned into the pEff vector yielded up to 200 µg/g of FW [311,312]. Both products confirmed that the truncated HEV capsid proteins expressed in plants are suitable for diagnostic purposes [310,312].…”
Section: Hepatitis E Virusmentioning
confidence: 68%
See 1 more Smart Citation
“…Examination of the HEV/RBD samples by electron and atomic force microscopy revealed VLPs with size of 30–40 nm, while dynamic light scattering detected ~40 nm particles and aggregates 200–300 nm in size ( Table 1 ). In comparison, the HEV 110-610 capsid protein without any fusion partners formed smaller particles with an estimated size of 18–26 nm ( Table 1 and [ 71 ]).…”
Section: Resultsmentioning
confidence: 99%